1998
DOI: 10.1128/jcm.36.12.3619-3623.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR for Detection of DNA Specific for Aspergillus Species in Sera of Patients with Various Forms of Pulmonary Aspergillosis

Abstract: Pulmonary aspergillosis is classified into invasive, saprophytic, and allergic forms. In this study, we evaluated the usefulness of PCR for differentiating between different forms of aspergillosis or in monitoring disease activity during treatment by detecting DNA specific for Aspergillus species in the serum. Nested PCR was used to detect Aspergillus DNA in the sera of 30 patients with various forms of pulmonary aspergillosis. The results were compared with those of latex agglutination tests for detecting gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…It does appear that, as in case of patient O, the infection is detected one week and not the next. This phenomenon has been reported (Van Burik et al , 1998; Yamakami et al , 1998; Lass‐Flörl et al, 2001). The ability of the PCR to detect Aspergillus may have been affected by the presence of antifungal drugs.…”
Section: Discussionsupporting
confidence: 69%
“…It does appear that, as in case of patient O, the infection is detected one week and not the next. This phenomenon has been reported (Van Burik et al , 1998; Yamakami et al , 1998; Lass‐Flörl et al, 2001). The ability of the PCR to detect Aspergillus may have been affected by the presence of antifungal drugs.…”
Section: Discussionsupporting
confidence: 69%
“…Tests are also available to detect aspergillus antibodies (120,121); however, these tests depend on a normal host immune response, which is absent in immunosupressed patients. A polymerase chain reaction test to detect DNA of Aspergillus species has been developed (122)(123)(124).…”
Section: Invasive Aspergillosismentioning
confidence: 99%
“…A number of previous studies evaluating PCR‐mediated detection of Aspergillus species showed significantly improved sensitivity but involved assays with different methods and objectives, partly to optimize culture assays, partly for typing in epidemiological studies (Aufauvre‐Brown et al , 1992; van Belkum et al , 1993; Girardin et al , 1994; Anderson et al , 1996; Rath et al , 1996; Brandt et al , 1998; Fletcher et al , 1998; Radford et al , 1998). Studies with clinical samples, such as blood or BAL, were mostly done retrospectively and, with few exceptions, with small numbers of patients (Spreadbury et al , 1993; Tang et al , 1993; Makimura et al , 1994; Melchers et al , 1994; Bretagne et al , 1995, 1998; Verweij et al , 1995a; Walsh et al , 1995; Kappe et al , 1996; Yamakami et al , 1996, 1998; Einsele et al , 1997, 1998; Jones et al , 1998; Van Burik et al , 1998; Kawamura et al , 1999; Skladny et al , 1999). Results from recent studies screening blood samples from high‐risk patients with PCR assays seem promising to identify a population at highest risk for invasive fungal disease (Einsele et al , 1998; Hebart et al , 2000a,b; Lass‐Flörl et al , 2001).…”
mentioning
confidence: 99%